2022
DOI: 10.3389/fphar.2022.863667
|View full text |Cite
|
Sign up to set email alerts
|

The Inflammation in the Cytopathology of Patients With Mucopolysaccharidoses- Immunomodulatory Drugs as an Approach to Therapy

Abstract: Mucopolysaccharidoses (MPS) are a group of lysosomal storage diseases (LSDs), characterized by the accumulation of glycosaminoglycans (GAGs). GAG storage-induced inflammatory processes are a driver of cytopathology in MPS and pharmacological immunomodulation can bring improvements in brain, cartilage and bone pathology in rodent models. This manuscript reviews current knowledge with regard to inflammation in MPS patients and provides hypotheses for the therapeutic use of immunomodulators in MPS. Thus, we aim t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 145 publications
0
16
0
Order By: Relevance
“…For this purpose, in brief, the following steps were taken to develop the decision model: Firstly, a comprehensive literature review identified the most promising treatment targets (the TLR4 cascade with the NLRP3 inflammasome) [ 7 ] and immunomodulatory drugs that target these. Secondly, a quantitative RBA of the most relevant drugs was performed following the DAF methodology, which will be described in the remainder of the methods section.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, in brief, the following steps were taken to develop the decision model: Firstly, a comprehensive literature review identified the most promising treatment targets (the TLR4 cascade with the NLRP3 inflammasome) [ 7 ] and immunomodulatory drugs that target these. Secondly, a quantitative RBA of the most relevant drugs was performed following the DAF methodology, which will be described in the remainder of the methods section.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, therapeutic alternatives are urgently needed, and an increasingly better understanding of the underlying cell mechanism has revealed a number of potential treatment targets [ 7 , 8 , 9 , 10 ]. The most promising ones include the Toll-like receptor (TLR) family, most notably TLR-4, as well as the resulting transcription of pro-inflammatory proteins via NF-κB and the final activation of the NLRP3 inflammasome [ 7 ]. Despite a limited number of pre-clinical and small clinical studies, these approaches have not been clinically established so far.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been recognized that inflammatory processes play a major role in MPS. This offers a range of targets to intervene with immunomodulators, such as anakinra, adalimumab, or abatacept, as potential adjuvant therapeutic options [ 32 ]. However, research regarding adjuvant therapeutic options is particularly hampered in MPS.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Although the disease seems to originate from abnormal storage of GAGs, it is now accepted that the primary GAGs storage triggers a pathogenic cascade, with many other factors involved, including inflammation. 3 …”
Section: Introductionmentioning
confidence: 99%
“…2 Although the disease seems to originate from abnormal storage of GAGs, it is now accepted that the primary GAGs storage triggers a pathogenic cascade, with many other factors involved, including inflammation. 3 Patients with MPS may present severe manifestations that could include non-immune hydrops fetalis (NIHF) 4 and/or early neurodegeneration, or have a more attenuated phenotype that could be marked by corneal clouding and mild bone and joint abnormalities. 5 This heterogeneity is clear not only across the different MPS types but also within the same type, with different variants and levels of residual enzyme activity.…”
Section: Introductionmentioning
confidence: 99%